Characterization of bubbles dynamics in aperiodic formation. (December 2021) - Farhat, Mohamad; Chinaud, Maxime; Nerisson, Philippe; Vauquelin, Olivier
Highlights: Bubble-bubble interactions leading to aperiodic formation at high flowrates. Classification of bubbling regimes depending on the position of bubbles' coalescence. Tracking the bubbles formation, coalescence, and the formation of the globules. Developing of phenomenological approach that characterize the volume of globules. Importance of phenomenological approach to determine bubble volumes contrary to classical approaches. Abstract: Bubble-bubble interactions are relevant to industrial applications, for which air is injected at different flowrates from submerged orifice. These interactions provoke aperiodic bubble formation that affects their departure and size distribution, which is revealed through our experimental data. Air is injected and regulated at flow rate between 10 −4 m 3 .s −1 and10 −3 m 3 .s −1 from a submerged orifice of inner diameter 12 mm, corresponding to a gas Weber number between 0.16 and 16. Image analysis is carried out to track the formation and departing of bubbles, as well as the formation of a globule, which is a large bubble formed after the bubbles coalescence. Upon increasing the flowrate, the different patterns of bubbling observed have been classified according to the variation of the coalescence position. In a conventional method, bubbles volumes are determined by inspecting the departure frequency and assuming single bubbling spherical pattern. Using the same assumptions and method, we find a good agreement with literature models. Owing to the phenomenological description of the flow, the frequency and volume of globules are characterized. A contrast between the conventional and phenomenological approaches is exposed, revealing a weak applicability of conventional models in estimating bubbles sizes at high flow rates.